The Role of Organizational Culture, Leadership Behavior, and Job Satisfaction in Enhancing Teacher Productivity in Early Childhood Education Management - Budimayansah, Bambang Lestrika; Ananda, Rusydi; Khadijah, Khadijah (Newinera Publisher, 2025)
This study aims to analyze the influence of organizational culture, leadership behavior, and job satisfaction on the work productivity of kindergarten teachers in Binjai City. Using a quantitative research approach, data were collected through questionnaires distributed to 120 teachers across several early childhood education institutions. The data were analyzed using descriptive statistics, reliability tests, and multiple regression analysis. The results revealed that all three independent variables significantly affect teacher productivity, both partially and simultaneously. The coefficient of determination (R²) value of 0.726 indicates that 72.6% of productivity variation is explained by these factors, while job satisfaction emerged as the most dominant variable. The findings suggest that a strong organizational culture promotes discipline and cooperation, effective leadership encourages motivation and commitment, and job satisfaction enhances enthusiasm and performance. Overall, the synergy among these three aspects creates a conducive and productive educational environment for early childhood teachers. This study emphasizes the importance of strengthening organizational culture, applying transformational leadership, and improving job satisfaction to optimize teacher productivity in early education institutions.